Effectiveness of Online Psychotherapy in Managing Mental Health Problems During The Covid-19 Pandemic: A Systematic Review - Nur Annisa Ilmiatun; Nur Arifah Astri; Mea Kuraini Syafitri (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Psychosisocial problems such as anxiety, depression, and psychological trauma are one of the impacts of the COVID-19 pandemic. So that psychotherapy is needed which allows it to be applied during the COVID-19 pandemic. This study aimed to determine the effectiveness of online psychotherapy in dealing with mental health problems during the COVID-19 pandemic. Methods: A systematic search of 4 databases (Scopus, Sciencedirect, Spingerlink, and SAGE) was conducted. Studies published in English from 2016 to 2021 were considered. Ten studies with mental health problems at the time of a pandemic further identified. There are several types of therapy applied to studies such as Mindfulness in Motion (MIM) and Cognitive Behavior Therapy (CBT) via the internet, online, the Zoom platform, and the telephone. People with mental health problems experience benefits from online psychotherapy. Several studies have conducted continuous monitoring of results to ensure long-term effectiveness of therapy